2016
DOI: 10.1007/s00268-016-3585-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Percutaneous Cholecystostomy for Acute Cholecystitis

Abstract: PC is effective and relatively safe in high-risk patients with AC. However, patients with higher ALP or AMI during index admission have higher risk of recurrence and might benefit from definitive cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
35
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 22 publications
6
35
0
4
Order By: Relevance
“…26 In addition, several recent studies have suggested not only the traditional role of PC as bridging therapy, but also its potential role as definitive therapy for AC. [22][23][24][25][26] These suggestions are based on the relatively low recurrence rates of AC after PC without subsequent cholecystectomy in the aforementioned studies (ranging from 9.2% to 23.5%), which is comparable with those values in the present study (elderly group 19.3%, non-elderly group 20%). Given the relatively low mortality and low recurrence rates of AC after PC, this technique appears useful as a definitive first-line treatment without subsequent cholecystectomy in elderly AC patients with various comorbidities.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…26 In addition, several recent studies have suggested not only the traditional role of PC as bridging therapy, but also its potential role as definitive therapy for AC. [22][23][24][25][26] These suggestions are based on the relatively low recurrence rates of AC after PC without subsequent cholecystectomy in the aforementioned studies (ranging from 9.2% to 23.5%), which is comparable with those values in the present study (elderly group 19.3%, non-elderly group 20%). Given the relatively low mortality and low recurrence rates of AC after PC, this technique appears useful as a definitive first-line treatment without subsequent cholecystectomy in elderly AC patients with various comorbidities.…”
Section: Discussionsupporting
confidence: 90%
“…A systematic review in 2009 reported that the mortality rate after PC (overall 15.4%, procedure‐associated 3.6%) was significantly higher than that after cholecystectomy (4.5%) in AC patients aged ≥65 years . However, recent reports have shown relatively low mortality rates after PC (0–8.5%), which is consistent with the findings in the present study (overall 3.6% [6/166], procedure‐associated 0%) . A recent review from Canada indicated that the reduction in the mortality rate after PC with time might be attributed to improvements in equipment and technique, operator use, increased imaging quality, better supportive care, and improved patient selection .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Only one retrospective study reported long-term mortality of 71 patients with a median follow-up of 37 months and an overall mortality rate of 32% during that time period, 24 which is consistent with our overall 2-year survival rate of 35% in the cholecystostomy group and 41% in the no cholecystostomy group. The poor long-term survival data reflect the underlying severity of comorbid illness.…”
Section: Discussionsupporting
confidence: 87%